Immune-Mediated Antitumor Activity of Reovirus Is Required for Therapy and Is Independent of Direct Viral Oncolysis and Replication - Prestwich, Robin J. (Clin Cancer Res, 2009)
PURPOSE: Reovirus is a naturally occurring oncolytic virus in clinical trials. Although tumor infection by reovirus can generate adaptive antitumor immunity, its therapeutic importance versus direct viral oncolysis is undefined. This study addresses the requirement for viral oncolysis and replication, and the relative importance of antitumor immunity and direct oncolysis in therapy. EXPERIMENTAL DESIGN: Nonantigen specific T cells loaded with reovirus were delivered i.v. to C57BL/6 and severe combined immunodeficient mice bearing lymph node and splenic metastases from the murine melanoma, B16ova, with assessment of viral replication, metastatic clearance by tumor colony outgrowth, and immune priming. Human cytotoxic lymphocyte priming assays were done with dendritic cells loaded with Mel888 cells before the addition of reovirus. RESULTS: B16ova was resistant to direct oncolysis in vitro, and failed to support reovirus replication in vitro or in vivo. Nevertheless, reovirus purged lymph node and splenic metastases in C57BL/6 mice and generated antitumor immunity. In contrast, reovirus failed to reduce tumor burden in severe combined immunodeficient mice bearing either B16ova or reovirus-sensitive B16tk metastases. In the human system, reovirus acted solely as an adjuvant when added to dendritic cells already loaded with Mel888, supporting priming of specific antitumor cytotoxic lymphocyte, in the absence of significant direct tumor oncolysis; UV-treated nonreplicating reovirus was similarly immunogenic. CONCLUSION: The immune response is critical in mediating the efficacy of reovirus, and does not depend upon direct viral oncolysis or replication. The findings are of direct relevance to fulfilling the potential of this novel anticancer agent.